2004
DOI: 10.1002/ptr.1273
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive brominated diterpenes from the marine red alga Jania Rubens (L.) Lamx.

Abstract: Seven brominated diterpenes of the parguerene and isoparguerene series were isolated for the first time from the red alga Jania rubens (L.) Lamx., collected from the Red Sea coast at Hurghada, Egypt. The diterpenes were identified as isoparguerol (1), isoparguerol-16-acetate (2), isoparguerol-7,16-diacetate (3), parguerol-16-acetate (4), parguerol-7,16-diacetate (5), deoxyparguerol (6) and deoxyparguerol-7-acetate (7). The isolated diterpenes had a marked antitumour activity. Isoparguerol derivatives were slig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 9 publications
(17 reference statements)
1
41
0
Order By: Relevance
“…Several brominated diterpenes of the parguerenes and isoparguerenes isolated from red alga Jania rubens were reported to have antitumor, anti-helmintic, and antimicrobial activities [51]. Parguerene derivatives with cytotoxic activity on P388 and HeLa tumor cells possessed an acetoxy group at C-2 and a bromine at C-15 [52].…”
Section: Parguerenes and Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several brominated diterpenes of the parguerenes and isoparguerenes isolated from red alga Jania rubens were reported to have antitumor, anti-helmintic, and antimicrobial activities [51]. Parguerene derivatives with cytotoxic activity on P388 and HeLa tumor cells possessed an acetoxy group at C-2 and a bromine at C-15 [52].…”
Section: Parguerenes and Derivativesmentioning
confidence: 99%
“…Interestingly, the synthetic analogs 46-50 were shown to significantly sensitize the HCT116/VM46 human colorectal carcinoma cell overexpressing P-gp to vinblastine and doxorubicin better than the marine natural product 45 and verapamil [114]. Studies of the N-aryl homologs of 45 (50)(51) revealed that increasing the carbon linker leads to increase in activity. The authors concluded that the N-alkylaryl substituent is necessary for activity, but the analogs which bear free phenolic groups and methyl esters are more cytotoxic and lack potent MDR reversal properties.…”
Section: Ningalins and Derivativesmentioning
confidence: 99%
“…agrotec., Lavras, v. 36, n. 3, p. 294-299, maio/jun., 2012TEIXEIRA, 1999. Important examples of bioactive halogenated terpenes are (i) laurenditerpenol, isolated from Laurencia intricata, which inhibits angiogenesis process (MOHAMMED et al, 2004), and (ii) 7-ethyl desoxiparguerol, isolated from Jania rubens, which shows anthelmintic activity and is effective against Ehrlich carcinoma (AWAD, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Also, compounds in the diethyl ether fraction, in particular terpenoids, were shown to suppress proliferation of many types of tumours (in vitro) (Awad, 2004).…”
Section: Antioxidant Capacity Of Algal Extractsmentioning
confidence: 99%